2016
DOI: 10.3390/catal6090139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Sb-Doped SnO2 Support on the CO-Tolerance of Pt2Ru3 Nanocatalysts for Residential Fuel Cells

Abstract: Abstract:We prepared monodisperse Pt 2 Ru 3 nanoparticles supported on carbon black and Sb-doped SnO 2 (denoted as Pt 2 Ru 3 /CB and Pt 2 Ru 3 /Sb-SnO 2 ) with identical alloy composition and particle size distribution by the nanocapsule method. The activities for the hydrogen oxidation reaction (HOR) of these anode catalysts were examined in H 2 -saturated 0.1 M HClO 4 solution in both the presence and absence of carbon monoxide by use of a channel flow electrode at 70 • C. It was found that the CO-tolerant H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…As has been observed for the CO adsorption process on various catalysts, the changes in the IR spectra in Figure 4 indicate that the bands consists of multiple components, which can be ascribed to CO ad in slightly different configurations or environments, specifically, terraces or step/edge sites [12,13]. [7,[12][13][14]. A small band around 1950 cm −1 on c-Pt2Ru3/C (see Figure 5) was assigned to COad in a bridged configuration on Pt-Ru and/or Ru-Ru sites [CO-Ru, COB(Pt-Ru) or COB(Ru-Ru)] [13].…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…As has been observed for the CO adsorption process on various catalysts, the changes in the IR spectra in Figure 4 indicate that the bands consists of multiple components, which can be ascribed to CO ad in slightly different configurations or environments, specifically, terraces or step/edge sites [12,13]. [7,[12][13][14]. A small band around 1950 cm −1 on c-Pt2Ru3/C (see Figure 5) was assigned to COad in a bridged configuration on Pt-Ru and/or Ru-Ru sites [CO-Ru, COB(Pt-Ru) or COB(Ru-Ru)] [13].…”
Section: Introductionsupporting
confidence: 60%
“…The difference in the CO-tolerance will be discussed in more detail below. By the use of an in situ FTIR cell with the attenuated total reflection configuration (ATR-FTIR) [7,12], the IR spectra on both catalysts at 0.02 V (practical operating potential in PEFCs) versus an RHE and 60 • C by bubbling 1% CO (H 2 -balance) continuously in 0.1 M HClO 4 solution were measured together with the HOR current. The electrolyte solution was first saturated with pure H 2 to measure the initial HOR current and the reference IR spectrum at 0.02 V, followed by changing the gas to 1% CO/H 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,18,24 The CO ad oxidation rate is enhanced further by elevating the temperature or employing an oxide support (e.g., 0.21 V on Pt 2 Ru 3 /Sb-SnO 2 at 70°C). 21 On the other hand, we found that Pt skin/Pt-M alloys (M = Fe, Co, Ni, etc.) exhibited moderate CO-tolerant HOR activities at temperatures7 0°C.…”
Section: Co-tolerant Hor Mechanism At Pt-alloysmentioning
confidence: 74%
“…[1][2][3][4] For PEFC anode and cathode catalysts, the activity and its degradation have been analyzed by multilateral techniques such as X-ray photoelectron spectroscopy combined with an electrochemical cell (EC-XPS), 2,[5][6][7][8] in situ Fourier-transform infrared spectroscopy (FTIR), [9][10][11][12][13][14][15][16][17][18][19][20][21][22] electrochemical quartz crystal microbalance (EQCM), [23][24][25][26] in situ scanning tunneling microscopy (STM), [27][28][29][30][31] in addition to conventional electrochemical measurements such as rotating disk electrode (RDE), [32][33][34] channel flow electrode (CFE), 21,35,36 and channel flow double electrode (CFDE) methods. [37][38][39][40][41][42] Based on these results, new practical catalysts have been synthesized.…”
Section: Introductionmentioning
confidence: 99%